Literature Review : Faktor-Faktor Yang Berhubungan Dengan Kejadian Ispa Pada Balita - Meni Anggrayani; Minarti Minarti; Jatu Laksmita Zuhria; Qoswatun Khoiria Zerli (JURNAL BIDANG ILMU KESEHATAN, 2026)
Acute Respiratory Infection (ARI) is one of the leading causes of morbidity and mortality among children under five, particularly in developing countries such as Indonesia. This study aims to identify the factors associated with the incidence of ARI in toddlers through a literature review. Articles were searched using databases including Google Scholar, PubMed, ScienceDirect, Garuda, and Neliti, focusing on publications from the past five years. A total of 20 articles that met the inclusion criteria were analyzed to identify the dominant risk factors influencing ARI incidence in young children. The review findings show that ARI in toddlers is influenced by multiple multifactorial determinants. The most consistently significant factors include exposure to cigarette smoke inside the home, poor ventilation and inadequate housing conditions, and household overcrowding. In addition, health-related behaviors such as lack of exclusive breastfeeding and incomplete immunization status were also found to increase the risk of ARI. Biological factors, including poor nutritional status and low birth weight, contribute further to children’s susceptibility. Maternal characteristics, particularly knowledge and education levels, also play an important role in ARI incidence by influencing child care practices and home environmental management. Overall, the review highlights that ARI prevention in toddlers requires a comprehensive approach through improved family health behaviors, enhanced household environmental quality, and optimized immunization coverage and nutritional intake. Such efforts are expected to reduce ARI incidence and prevent more severe complications among children under five.